If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x+3x-4x=4x-11
We move all terms to the left:
x+3x-4x-(4x-11)=0
We add all the numbers together, and all the variables
-(4x-11)=0
We get rid of parentheses
-4x+11=0
We move all terms containing x to the left, all other terms to the right
-4x=-11
x=-11/-4
x=2+3/4
| -0.845=(x-63)/12 | | 18-2=x-3x | | 18=14-2x | | 6x=4=16 | | 14-10=x | | 14-10-16=x | | -(4a+5)=15-2a | | x5+1=41 | | 4x=10-16 | | 7p-6|=|6p+32| | | 2(x-5)=4(3+x) | | 23=5x+8=28 | | 20x=-20+60 | | 10=30-3(-2-4w) | | x2-4x+4=ß | | 144q−15=0 | | 5/4v=-20 | | 4n=5=6n-7 | | 11b=9+98b | | 11b=9+98 | | 59c=78+33c | | 7/9y=-14 | | 4x^2+52x+40=0 | | 8/12•w=9 | | 2x+3-4=180 | | (Y/30)*10=x | | 0.02*x=200 | | X+8=1.5x-6 | | 23y=15y+48 | | 12+z=16 | | (9-x/6)*5=420 | | Y=15x/50 |